PENGARUH KEMAMPUAN AWAL DAN SOFT SKILLS TERHADAP HASIL BELAJAR KARTOGRAFI - nofrion nofrion (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2013)
Abstract The purpose of this study is to analyze data on the influence of initial ability and soft skills to the cartography learning outcomes, the influence of soft skills learning outcomes and influence the ability of early cartography and soft skills together on student learning outcomes at the course cartography. The type of research is a correlational descriptive research that looked at the relationship between one or several variables with one or more other variables. The independent variable is the ability to start and soft skills as well as the dependent variable is the result of studying cartography. The population in this study amounted to 193 people and the sample is 66 people selected by simple random sampling. Initial capability data and study results taken from the student while in high school geography class XII and class X semester 1 semester 1 and 2 and the UN geography subjects. Soft Skills While data collected through a structured questionnaire with Likert Scale models. Prior to the analysis carried out the analysis of test requirements test for normality, homogeneity, linearity and multicollinearity. After that, an analysis of descriptive and inferential statistics. The technique used is the correlation and regression. The results revealed: 1). Initial ability affects the outcome of student learning in cartography courses at 14, 00%, 2). Soft Skills effect on student learning outcomes in Cartography course at 24, 30%, 3). Initial ability and soft skills together influence the learning outcomes of students in cartography courses of 32, 40%. Based on the above result, it is to improve student learning outcomes in cartography courses in the Department of Geography, Faculty of Social Science, State University of Padang needs to consider the initial ability and soft skills. Therefore, provisions need to be clear about the entry requirements to the department of geography for high school graduates and educators in this study need to device balanced learning between hard skills with soft skills. This can be done by integrating aspects of soft skills into learning